Assessment of geoecological conditions in Son La province (Vietnam) and natural risk prevention - T. N. Nguyen; V. N. Ekzaryan (Известия высших учебных заведений: Геология и разведка)
Introduction. Shonla is a mountainous province located in the northwestern region of Vietnam, has a complex and diverse terrain with many shapes of hills, valleys and rivers. The assessment of the state of the geo-ecological conditions of the province of Shonla contributes to the development by government agencies of measures aimed at the protection and rational use of the natural environment, which is the basis for the transition to a model of sustainable development and prevention of risks caused by geological processes.Aim. Studying and assessing the current state of the geoecological conditions in Son La province, Vietnam and the proposal of measures for the transiton to models of sustainable development of the territory.Materials and methods. To obtain information about the geoecological conditions of the territory of the province of Shonla, all previously performed geological, geographical, geodynamic, hydrogeological and other studies were collected, analyzed and summarized. Special attention was paid to the collection of materials for assessing the state and degree of activity of exogenous geological processes. The field research, which was carried out with the participation of one of the authors, included a large complex of geological, hydrogeological, geophysical, hydrological and other methods. Data reflecting the current state of the geoecological conditions of the territory and the degree of impact of the existing functional infrastructure on the environment as a whole were obtained. Remote sensing materials were used to assess the geoecological condition of the territory of Shonla province.Results. The province of Shonla is a hilly area with steep slopes located along a system of fast-flowing rivers, which creates complex geoecological conditions and indicates the possibility of various geological processes and phenomena that pose a danger during the functional development of the territory. At the same time, Shongla is a territory with favorable conditions for the development of various types of natural ecotourism, which is currently actively developing in Vietnam. The main groups of natural resources located in the territory of Shonla province include land, forest and mineral resources. The study of the geoecological conditions of the province of Shonla (relief and geomorphology, geological structure, hydrogeology, mineral resources) made it possible to identify environmental problems arising from the use of the territory and propose measures for the transition to a model of sustainable development of the region.Conclusions. In the process of geological development of the territory, the characteristic features of the relief of the province of Shonla were formed. The territory is located in a region with a complex geological structure and the presence of large tectonic fault systems, which increases the risk of geological processes such as earthquakes, flash floods, landslides and others. The assessment of geoecological conditions is a scientific and methodological basis for the development and implementation of measures to prevent natural risks. In order to preserve the unique natural resources, it is necessary to develop and implement a regional model for the transition to sustainable development of the province of Shonla. The results obtained in the course of research can be directly used in construction projects, transport and management structures, as well as in planning the socio-economic development of settlements located in the province of Shonla.